Ocean! : [book with audioplayer] waves for all - McAnulty, Stacy (McAnulty, Stacy. Our universe., 2021)
"Dude, I am Ocean. You know my many names: Atlantic, Pacific, Arctic, Indian, Southern. It's all excellent me. My salt water flows across the planet as one. I have no flag. No nationality. My waves are for all. Life on Earth began in my epic waters I keep the global climate just right. And I have rad secrets. But I'm facing a major wipeout! Only by working together can we get back in the zone. It's you and me, dudes."--